Sistem pangan dalam pertanian berkelanjutan - Larasati, Kinanti (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Food systems have issues such as the governance and economics of food production, sustainability, how food is disposed of, how food production affects the environment, and the impacts on the health of individuals and populations from the food. Findings: Agriculture currently faces major challenges worldwide, including feeding a growing world population, managing ecosystem goods and services in response to a changing global environment, and reducing poverty. The food systems approach has been widely used to identify, analyze and assess the impacts of system activities and outcomes to help identify intervention points to improve food security. Methods: This study uses a case study with data sources through primary and secondary data supported by the interview technique used. Conclusions: Recommendations for a sustainable food system are made through the formation of a more detailed sustainable food system policy that looks at environmental, social and economic aspects; optimizing the use of local food by ensuring the availability of land and water; inclusive access as food; applying the concept of sustainability to the food system cycle from upstream to downstream; expanding the diversity of staple food types and ensuring quality and nutrition; developing food barns with local wisdom and involving the community; maintaining food prices in each value chain; forming a lifestyle of consuming food responsibly; and minimize food waste.